(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
In the past decades, sound and audio technologies have gained a central role in theatrical research, giving rise to new performative forms that have consolidated three current trends: the exploration of non-traditional places, the audience participation in the performance and in the creation of the dramaturgy, and the use of technologies to activate new modes of perception, interaction and relationship. This article explores the origins, the development and impact of the SilentPlay, a sound-based theatrical format focused on the use of headphones technology started in 2009 by the theatre company La Piccionaia. In this sonic dramaturgy, participants are guided in the exploration of places by a performer-conductor who, through the use of wireless headphones, transmits audio tracks and stimulates the interaction of the participants. The article analyses the connections of this project with the experimentations of children’s theatre, participatory theatre and sound walks; describing its two main research directions: the co-creation of place-based narratives and the development of remote directed performances. The experience of the SilentPlay suggests the possibility for sound to be not only a complementary medium, but a primary element of creative production, which can inspire also other cultural engagement practices.